7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings - Harth, Florian Maximilian; Hočevar, Brigita; Grilc, Miha; Likozar, Blaž; Horvat, Barbara; Tesovnik, Anže; Mušič, Branka; Tominc, Sara; Karlovits, Mirica; Likozar, Blaž; Novak, Uroš; Kokol, Nino; et al. (2025)
The 7th International Conference on Technologies & Business Models for Circular Economy (TBMCE) was organized by the Faculty of Chemistry and Chemical Engineering of the University of Maribor in collaboration with the Strategic Research and Innovation Partnership – Networks for the transition into circular economy (SRIP – Circular economy), managed by the Chamber of Commerce and Industry of the Štajerska. The event took place from September 4 to 6, 2024 in Portorož, Slovenia, at the Grand Hotel Bernardin. The conference focused on the current challenges and opportunities related to technological development and society's responsibility in the transition to a more sustainable and circular management of resources. The conference program included a round table on "Circular Economy Transition in the South-East Europe", 5 panel discussions, plenary and 2 keynote speeches as well as oral and poster presentations. The conference was held under the patronage of the Ministry of the Economy, Tourism and Sport and the Ministry of Cohesion and Regional Development. EIT RawMaterials RIS Hub Adria, SPIRIT Slovenia Business Development Agency, and Pomurje Technology Park (as part of the GREENE 4.0 and CI-Hub projects) joined us as co-organizers.
Keywords: circular economy; sustainable development; processes and technologies; circular business models; research and development